The Effect of Wordwall on Bilingual Mathematics Learning Motivation in Elementary School - Muhimmatul Ulya; Aris Kuswanto (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2026)
This study examined changes in elementary students' motivation after the implementation of Wordwall in bilingual mathematics learning. This study used a quantitative pre-experimental one-group pretest-posttest design. The participants were 28 fourth-grade students at MI Bilingual Roudlotul Jannah Sidoarjo, Indonesia. Data were collected using a learning motivation questionnaire based on Keller's ARCS model, which includes Attention, Relevance, Confidence, and Satisfaction. The instrument was validated using Pearson's Product-Moment correlation and tested for reliability using Cronbach's Alpha. The data were analyzed using descriptive statistics, N-Gain analysis, the Shapiro-Wilk normality test, a paired sample t-test, and Cohen's effect size. The findings showed that students' mean motivation score increased from 63.18 in the pretest to 87.79 in the posttest. The N-Gain score was 0.6794, indicating moderate improvement. The paired-samples t-test showed a significant difference between the pretest and posttest scores, and Cohen's dz indicated a very large effect size. These findings suggest that Wordwall can serve as a promising interactive digital learning medium for supporting students' motivation in bilingual mathematics learning. However, because this study used a pre-experimental design without a control group, the results should be interpreted as evidence of motivational improvement within the observed classroom rather than as definitive causal proof of Wordwall's effectiveness.